38 Floor Apartment Design With Special Moment Frame System (SMF), With Performance Based Design Using SNI 1726: 2019 and SNI 1729: 2015 - Achmad Ubaidillah; Tony Hartono Bagio; Julistyana Tistogondo (Neutron, 2021)
Apartments are an option for vertical housing. Currently, with the rapid development of technology, a person will tend to choose housing that can support their mobility. So it is planned that an apartment building structure is planned using a Special Moment Frame System using Performance Based Design referring to SNI 1729: 2015 and SNI 1726: 2019. Planned with columns HC 582x500x50x65 and HC 508x462x75x75 as well as WF beams 400x300x12x22 and WF 400x200x12x22. The results show that the columns and beams are strong but wasteful.